Proceedings of the 14th International ACM SIGACCESS Conference on Computers and Accessibility 2012
DOI: 10.1145/2384916.2384923
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for technology that support physical activity by older adults

Abstract: Barriers to physical activity prevent older adults from meeting recommended physical activity levels necessary for maintaining quality of life. As technology becomes more advanced, we have the opportunity and the responsibility to address concerns faced by the aging population. We seek opportunities for technology to empower older adults to overcome barriers on their own by interviewing and learning from older adults who have successfully overcome these barriers. In this paper, we present a set of needs that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…The use of metaphors and avatars is common and reasonable in game design, but also in persuasive design: showing physical activity levels as, for example, a flower, 43 a garden, 44,45 or art. 46 Such metaphorical displays are in general well accepted and positively received. [43][44][45][46][47] Lin et al 27 specifically showed that exhibiting activity through the growth and emotional state of virtual fish indeed increased users' awareness of their levels of physical activity and increased their motivation to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The use of metaphors and avatars is common and reasonable in game design, but also in persuasive design: showing physical activity levels as, for example, a flower, 43 a garden, 44,45 or art. 46 Such metaphorical displays are in general well accepted and positively received. [43][44][45][46][47] Lin et al 27 specifically showed that exhibiting activity through the growth and emotional state of virtual fish indeed increased users' awareness of their levels of physical activity and increased their motivation to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The game features a virtual instructor who shows poses that should be imitated by the player, and the system applies wearable sensors to determine and evaluate user input; the authors do not provide any information on the evaluation of the system. Fan et al 50 present Spark, a pedometer-based system similar to Flowie 29 ; however, instead of combining pedometer input with a game, they provide visualizations of user activity. A three-week qualitative evaluation during which participants used the system and participated in interviews showed that people enjoyed using the system, and that it provided them with useful feedback on their daily activity.…”
Section: Exertionmentioning
confidence: 99%
“…A growing number of projects focus on the development of accessible motion-based applications for older adults with the goal of providing physical and mental stimulation [7], e.g., for people living in nursing homes. Full-body motion-based games usually require players to be able to stand without assistance and move around in the room freely.…”
Section: Motion-based Game Controls For Older Adultsmentioning
confidence: 99%